Impact of Digital Skills on Faculty in Teaching and Research: A Case of GC University Lahore, Pakistan - Khuram Shahzad (IJoLIS, 2024)
Purpose:To know the impact of digital skills and related barriers on faculty of Government College University (GCU) Lahore in thier teaching and research.